Pertumbuhan Tanaman Pisang Kepok (Musa paradisiaca L.) pada Berbagai Konsentrasi BAP Secara In Vitro - Zarmiyeni Zarmiyeni; Mahdiannoor; Lisa Lisa (Rawa Sains: Jurnal Sains STIPER Amuntai, 2014)
Bananas are one of the horticultural commodities is very popular in the world because it was delicious, the price is relatively cheap and have high nutritional value. Production of banana plants in Hulu Sungai Utara still relatively low because only bananas cultivated on a small and not available the procurement of seeds. To overcome these obstacles do necessary aside propagated using tissue culture techniques. ZPT which are often used to stimulate the formation of shoots in vitro culture banana is cytokinin as BAP. Cytokines in vitro culture has two important roles that stimulate cell division and the formation and propagation of axillary buds and adventitious buds, but the optimum levels of cytokines that can inhibit the growth and root formation. The purpose of this study is to get (i) the effect of various concentrations of BAP on plant growth kepok banana in vitro, (ii) the best BAP concentration for plant growth kepok banana in vitro. This research was conducted in tissue culture laboratory STIPER Amuntai in April 2013 to August 2013 using a completely randomized design (CRD) single factor with 5 treatments and 4 replications, so there are 20 experimental units. Each experimental unit consisted of 2 explants as a sample. Factors that are tested various concentrations of BAP are b1 : 2 mg / l, b2 : 3 mg / l, b3 : 4 mg / l, b4 : 5 mg / l, b5 : 6 mg / l. The results showed that percentage grows, the percentage of shoot formation, root formation percentage, number of shoots and number of leaves had no effect on treatment.